Camu-camu seed (Myrciaria dubia) – From side stream to an antioxidant, antihyperglycemic, antiproliferative, antimicrobial, antihemolytic, anti-inflammatory, and antihypertensive ingredient. (25th April 2020) - Fidelis, Marina; do Carmo, Mariana Araújo Vieira; da Cruz, Thiago Mendanha; Azevedo, Luciana; Myoda, Takao; Miranda Furtado, Marianna; Boscacci Marques, Mariza; Sant'Ana, Anderson S.; Inês Genovese, Maria; Young Oh, Won; Wen, Mingchun; Shahidi, Fereidoon; et al.
Graphical abstract: Highlights: Camu-camu seed extracts are rich sources of antioxidant phenolics. Extraction was optimised in terms of solvent mixtures (H2 O, EtOH, propanone). Optimised extract (OE) inhibited lipid oxidation and inhibited carbohydrate enzymes. OE presented cytotoxic effects towards HCT8 and A549 cells. OE protected human erythrocytes against hemolysis and had antyhypertensive activity. Abstract: Camu-camu ( Myrciaria dubia ) seeds are discarded without recovering the bioactive compounds. The main aim of the present work was to optimise the solvent mixture to extract higher total phenolic content and antioxidant capacity of camu-camu seeds. The optimised solvent system increased the extraction of phenolic compounds, in which vescalagin and castalagin were the main compounds. The optimised extract displayed antioxidant capacity measured by different chemical and biological assays, exerted antiproliferative and cytotoxic effects against A549 and HCT8 cancer cells, antimicrobial effects, protected human erythrocytes against hemolysis, inhibited α-amylase and α-glucosidase enzymes and presented in vitro antihypertensive effect. Additionally, the optimized extract inhibited human LDL copper-induced oxidation in vitro and reduced the TNF-α release and NF-κB activation in macrophages cell culture. Thus, the use of camu-camu seed showed to be a sustainable way to recover bioactive compounds with in vitro functional properties.